Competitiveness of the head as a subject of the state service: professionall and managerial competences (Journal of actual problems of jurisprudence, 2018)
The article reveals the content of the key professional competencies of modern government executives, which influence the competitiveness of the structural divisions headed by them. According to the article, the head of the state body should not only master the necessary professional competencies, but also be able to apply them in work in which competence competitiveness competencies are inherent in the whole team.The article raises the most important for public administration practice questions about the resources with which the key professional competencies are formed and how favorable it is for the state apparatus. For effective implementation of labor duties, the manager needs to have a certain set of qualities, knowledgeand skills, which can be characterized as professional competences of the head.Article is devoted to a specification of the concept “professional competence of the head of publicauthority” on which readiness degree the orientation and efficiency of development of the called competencein many respects depends. Results of a research created the methodical and special competences,which are a part of professional competence of heads of public authorities, are given.About what competencesare necessary for the competitive head as they should be estimated and what measures canbe taken for development of professional competences of the head it is possible to read in this article.Key words: professional and managerial competences, competitiveness, competence, soft skills,abilities.